Synergetic Effect of Accentuated Cut Edges (ACE) and Macerating Enzymes on Aroma and Sensory Profiles of Marquette Red Wine - Yiliang Cheng; Aude A. Watrelot (Fermentation)
This research explored the effects of using Accentuated Cut Edges (ACE) and macerating enzymes on the aroma and sensory profile of Marquette red wines after nine months of aging. The aroma analysis was conducted using gas chromatography-mass spectrometry (GC-MS) with solid-phase microextraction (SPME). The intensity of basic sensory attributes, including color, aroma, taste, and mouthfeel, were evaluated by eight trained panelists through descriptive analysis using 15 cm line scales. ACE treatment affected the aroma compounds profile, as suggested by the increased response ratio of ethyl butanoate, ethyl 2-methylpropanoate, and ethyl 3-methylbutanoate. Statistically, it significantly intensified honey (by 1.6 times) and green apple (by 2.1 times) notes, as perceived by panelists, compared to the control during the sensory descriptive analysis. Regardless of the type of enzymes, combined ACE and enzymes treatment amplified the color intensity of wine by up to 71.4% as observed by panelists, though this was not captured by spectrophotometric measurements (p > 0.05) from the previous study. A lower concentration of ester-derived compounds was found in ACE with enzymes wines, which was associated with the lower intensity of fruity notes during the descriptive analysis. Notably, none of the treatments affected astringency perception, likely due to the low concentration and small molecular weight of condensed tannins, alongside changes in the composition of soluble polysaccharide in Marquette red wines.